An International Atherosclerosis Society Position Paper: Global recommendations for the management of dyslipidemia—Full report - Grundy, Scott M.; Arai, Hidenori; Barter, Philip; Bersot, Thomas P.; Betteridge, D. John; Carmena, Rafael; Cuevas, Ada; Davidson, Michael H.; Genest, Jacques; Kesäniemi, Y. Antero; Sadikot, Shaukat; Santos, Raul D.; et al. (Journal of clinical lipidology, 2014)
An international panel of the International Atherosclerosis Society has developed a new set of recommendations for the management of dyslipidemia. The panel identifies non—high-density lipoprotein cholesterol as the major atherogenic lipoprotein. Primary and secondary prevention are considered separately. Optimal levels for atherogenic lipoproteins are derived for the two forms of prevention. For primary prevention, the recommendations emphasize lifestyle therapies to reduce atherogenic lipoproteins; drug therapy is reserved for subjects at greater risk. Risk assessment is based on estimation of lifetime risk according to differences in baseline population risk in different nations or regions. Secondary prevention emphasizes use of cholesterol-lowering drugs to attain optimal levels of atherogenic lipoproteins. ►International Atherosclerosis Society dyslipidemia guidelines are based on multiple lines of evidence.►Non–high-density lipoprotein cholesterol as a major form of atherogenic cholesterol.►Cardiovascular risk is adjusted according to baseline risk of different nations or regions.►Primary emphasis of guidelines is on lifestyle intervention; secondary emphasis on drug therapy.